The Principle of Legality and Legislative Intention. (11th December 2018) - French, Robert
Abstract: Contests about statutory interpretation frequently present courts with constructional choices. The process of choice is primarily volitional. An important principle directing constructional choice to the protection of common law rights and freedoms is the principle of legality. Historically, it is linked to a presumption about legislative intention. The presumption is at odds with contemporary legislative agendas and purports to link choice to a numinous concept of intention which plays no real part in interpretation, save as an after the event declaration of the legitimacy of the choice made. Text informed by context and statutory purpose remains central. The principle of legality properly stands alone without the aid of a presumed legislative intention.